Iconic Destiny and “The Lady of Shalott”: Living in a World of Images - McKelvy, William (Romanticism and Victorianism on the Net, 2007)
AbstractThis essay argues that “The Lady of Shalott” mirrors a moment in Britain’s age of industrialization when two machines in particular--the steam-press and the power-loom--had transformed ideas about intellectual and physical labor. Taking as a point of departure the poem’s well-documented visual canonization, I contend that non-verbal illustration is also a crucial historical category for understanding how the poem initially came to be. In this context, the many visual interpretations of “The Lady of Shalott” reflect Tennyson’s concerns about writing at a time when an illustrated print media had harnessed new powers of representation and replication.